Pengaruh Audit Tenure, Rotasi Audit, dan Spesialisasi Auditor Terhadap Kualitas Audit Pada BUMN Go-Public - Oktavia, Dzuhrini; Challen, Auliffi Ermian (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2022)
This study was conducted to examine the effect of audit tenure, audit rotation, and auditor specialization on audit quality. Where the study of audit quality is useful for users of financial statements and auditors in particular, as well as to add empirical evidence related to several factors that affect audit quality. The measurement of audit quality used in this study uses the discretionary accrual model of Kasznik (1999). This research is different from previous research, where this research was conducted in a Go-Public BUMN company listed on the Indonesia Stock Exchange. Samples were taken from the period 2016-2020 with a purposive sampling method. The research method used is a quantitative method, using secondary data from Go Public BUMN Companies listed on the Indonesia Stock Exchange. The results of the regression analysis show that audit tenure and audit rotation have no effect on audit quality. Meanwhile, auditor specialization has a positive effect on audit quality.